Why Energy Efficiency Matters and How to Scale It Up - Singh, Jas (World Bank, Washington, DC, 2016)
Energy efficiency is among the cheapest and cleanest energy resources available. The World Bank, together with its development partners and client governments, is making a commitment to ensure that energy efficiency becomes the “first fuel” of energy policy makers and governments around the world. This brief highlights lessons learned from two decades of energy efficiency programs in many countries. Five recommendations are offered at the end of the brief.